Investigating the Relationship between Financialization and Long-Term Use of Short-Term Debt - Seyed Reza Seyed Nezhad Fahim (Journal of Asset Management and Financing)
The purpose of this study is to investigate the relationship between financialization and financing maturity mismatch concerning the debt issues faced by Iranian firms, aiming to provide insights for managers and policymakers. The statistical sample consists of 143 active firms listed on the Tehran Stock Exchange over a ten-year period, from 2013 to 2022. The regression method was employed to estimate the models and test the research hypotheses. The findings indicate no significant relationship between financialization and the long-term use of short-term debt. However, distinct results emerged when firms were categorized into large and small entities. In large firms, financialization appears to positively affect the long-term use of short-term debt, in contrast to smaller firms. Additionally, financial constraints do not significantly influence the propensity of firms to utilize short-term debt and do not incentivize increased willingness among these firms to rely on short-term financing in the long term. Furthermore, financialization leads to a decrease in investment in productive assets, with firms that are more inclined toward financialization utilizing less internal financing. While previous studies on maturity mismatch have highlighted factors such as external regulations, the macroeconomic environment, and internal corporate governance, this study addresses a gap in the research concerning the discrepancy between corporate debt and investment horizons. It provides empirical evidence at the firm level and investigates the underlying mechanisms through which financialization influences the long-term use of short-term debt.Keywords: Capital Structure, Debt Maturity Structure, Financialization, Tangible Long-Term InvestmentsJEL Classification: G11، G31، P45  IntroductionAccording to the principle of matching investment and financing maturities, the maturity of a firm's debt should correspond to the maturity of its assets (Chen et al., 2023). The long-term use of short-term debt (LUSD) is a critical aspect of debt maturity mismatch, wherein short-term debt is allocated to support long-term investments. Analyzing the factors influencing LUSD is essential for gaining a comprehensive understanding of corporate financing decisions. The phenomenon of corporate financialization is prevalent globally and is closely linked to corporate investment and financing practices (Cao et al., 2022). Financialization may seem to reduce investment in fixed assets, potentially leading to diminished firm performance and economic recession (Tori & Onaran, 2018). Consequently, firms may encounter financing constraints, making it more challenging to secure long-term loans and resulting in an increased reliance on LUSD. Conversely, financialization may also be driven by hedging strategies and the pursuit of higher returns, which can alleviate financing constraints and improve firm performance, thereby reducing reliance on LUSD to some extent (Gong et al., 2023). Thus, the relationship between corporate financialization and LUSD remains ambiguous and warrants further investigation. This study aims to explore the relationship between financialization and financing maturity mismatch concerning the prevailing debt issues among Iranian firms, with the intent of providing insights for managers and policymakers. The findings are expected to offer valuable guidance for aligning fiscal policies, financing strategies, and investment initiatives. Materials & MethodsThe dependent variable of this study is the long-term use of short-term debt (LUSD), measured as the difference between the ratio of short-term liabilities to total liabilities and the ratio of short-term assets to total assets. Financialization serves as the independent variable, defined as the ratio of total financial assets to total assets. Financial assets encompass short-term and long-term investments, non-trade receivables, prepayments, and investments in real estate. Additionally, financial constraints are incorporated as an interactive variable, represented by a dummy variable. Firms with a financial cost-to-total debt ratio exceeding the median are classified as facing resource acquisition restrictions and assigned a value of one; otherwise, they are assigned a value of zero. The sample includes active firms listed on the Tehran Stock Exchange (TSE). The sample includes 143 firms over a ten-year period from 2013 to 2022. To explore the relationships among the variables, multiple linear regression analysis was conducted. The data were collected from firms' financial reports, the Codal system, and other reliable financial sources. Findings The findings indicate that, contrary to existing literature, there is no significant relationship between financialization and the long-term use of short-term debt (LUSD). However, when firms are categorized into large and small entities, distinct results emerge. In large firms, financialization has a positive effect on LUSD, whereas in small firms, financialization exerts a negative impact on LUSD. Additionally, the results suggest that financial constraints do not significantly influence the use of short-term debt and do not serve as an incentive for firms to increase their reliance on short-term financing in the long term. Furthermore, financialization is associated with a reduction in investment in productive assets. The findings also indicate that financialization diminishes firms' willingness to obtain internal financing. This suggests that firms inclined toward financialization are less likely to seek internal funds, thereby increasing their dependence on external borrowing. Discussion & Conclusion Given the high level of financialization in the sample firms, it is suggested that there should be an optimal degree of financialization, with careful consideration of the economic consequences of excessive financialization. In response to the current situation, it is recommended that enterprises focus on their core business, clarify their development priorities, and engage in financialization activities strategically at the micro level. Additionally, participation in corporate governance is essential. At the macro level, while guiding the development of the financial industry, it is also necessary to stimulate innovation in the economic value of enterprises and enhance their overall strength. Given the negative impact of financialization on investment in productive assets, it is crucial to foster a greater willingness and confidence among enterprises to invest in production units and encourage investment in the real economy. Governments and local institutions should effectively support enterprises by implementing robust policies for the real industry and creating a favorable business environment. Considering the positive impact of financialization on LUSD in large firms, managers are advised to rely more on long-term financing to better manage financial risk and working capital, thereby preventing default risk. Furthermore, in light of the negative impact of financialization on domestic financing—which diminishes its benefits—it is essential to streamline both direct and indirect financing channels for companies, improve the capital market environment, and expand the routes for long-term capital supply in the market.